A method for preparing a tensile test sample of a wire sample and a method for testing
Patent Information
- Application Number
- CN202611207170.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-23
AI Technical Summary
然而,这些方法要么效果有限无法根本解决问题,要么操作复杂不适用于批量测试
[0018]本发明的有益效果:本发明通过在金属丝线拉伸试样两端夹持部位电镀增粗,显著增大了夹持端的受力面积,有效降低了夹持端的应力集中,使拉伸断裂位置从夹持端转移至标距段内。与传统方法相比,本发明具有以下优势:其一,通过电抛光预处理彻底去除金属丝线表面的氧化膜,保证了镀层与金属基体之间的良好结合力,避免了镀层起皮、脱落的问题;其二,电镀过程中采用分段提升方式,避免液面处因电场分布不均产生应力集中,保证了镀层质量均匀性和拉伸试验的准确性;其三,该方法操作简便、成本低廉、效果可靠,可适用于直径0.1~10 mm的各类金属丝线拉伸试样的制备且无需对试验机夹具进行改造,也不需要复杂的试样夹持操作,具有广泛的适用性和推广价值。
Smart Images

Figure CN122961757A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of material tensile property testing technology, specifically relating to a method for preparing and testing tensile specimens of metal wire. The method involves pre-treating the clamping portions at both ends of the metal wire tensile specimen with electropolishing followed by electroplating to thicken the clamping ends, thereby increasing the diameter of the clamping ends and reducing stress concentration at the clamping ends, causing tensile fracture to occur within the gauge length. This invention is mainly applicable to the preparation and testing of tensile specimens of various metal wires, including pure aluminum wire, aluminum alloy wire, pure copper wire, copper alloy wire, and steel wire, and can significantly improve the success rate of metal wire tensile tests and the accuracy of test data. Background Technology
[0002] Metal and alloy wires are widely used in power cables, aerospace, electronic packaging, and medical devices due to their excellent mechanical, electrical, and thermal conductivity properties. In the production and quality control of metal wires, tensile testing is a crucial method for evaluating their mechanical properties (such as tensile strength and elongation). However, in actual tensile tests, thin-diameter metal wire specimens often break at the clamping end, rather than within the gauge length. This "breakage at the clamp" phenomenon severely impacts the success rate of tensile tests and the accuracy of test data, resulting in an inability to accurately reflect the material's mechanical properties.
[0003] The main reasons for this are as follows: First, most metal materials are relatively soft and have weak shear resistance. Under the clamping force of the testing machine jaws, the clamping end is prone to damage and stress concentration. Second, the clamping end of fine-diameter wires has a small force-bearing area. Under the same tensile load, the stress generated at the clamping end is much greater than that at the gauge length, causing the sample to break preferentially at the clamping end. Third, many metal wires have a dense natural oxide film on their surface (such as Al2O3 on the surface of aluminum and Cr2O3 on the surface of stainless steel). This oxide film has high hardness and electrical insulation, and it is difficult to completely remove it by conventional mechanical grinding. Moreover, after grinding, the metal surface will quickly re-oxidize in the air, which seriously affects the adhesion between the coating and the substrate in the subsequent electroplating process.
[0004] To address these issues, those skilled in the art have attempted various improvements, such as adjusting the clamping pressure, adding copper or aluminum pads to the clamping area, and using winding clamping. However, these methods either have limited effectiveness and fail to fundamentally solve the problem, or are too complex to be suitable for batch testing. Some researchers have also tried directly electroplating a metal layer at the wire clamping end, but due to the presence and differences in oxide films on different metal surfaces, the bonding force between the plating layer and the substrate varies significantly. This leads to peeling and flaking of the plating layer during electroplating, making it difficult to obtain a reliable plating quality. Furthermore, during electroplating, the uneven electric field distribution at the liquid surface can cause stress concentration at the contact point between the liquid surface and the wire after prolonged electroplating, making this area a weak point and causing premature breakage during tensile testing.
[0005] Therefore, after a long period of practice and exploration, a method for preparing and testing tensile specimens of metal wire has been developed. This method thoroughly removes the oxide layer on the surface of the metal wire through electropolishing pretreatment, and, in conjunction with a specific electroplating process and segmented lifting electroplating method, obtains a coating with good adhesion and uniform thickness at the clamping ends of the wire. Furthermore, by optimizing the tensile test parameters, the technical problem of metal wire fracture at the clamping end in tensile testing is fundamentally solved. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing and testing tensile specimens of metal wire. This method is characterized by its wide applicability and ease of operation, and it can effectively solve the problem of specimen breakage at the clamping end in tensile tests of metal wire.
[0007] To achieve the above objectives, the technical solution adopted by the present invention includes the following steps: a method for preparing a tensile specimen of a metal wire sample, comprising the following steps:
[0008] The first step is to cut the metal wire sample and remove oil stains from its surface. Cut the metal wire with a diameter of 0.1~10 mm to 15~30 cm, and then repeatedly wipe the metal wire sample with alcohol to remove the oil stains on its surface.
[0009] The second step involves pre-treatment of the plated areas at both ends of the metal wire sample through grinding and electropolishing. The clamping positions at both ends of the metal wire sample are marked as the plated areas. First, the plated areas are ground with 2000# sandpaper to remove the thicker oxide layer and burrs. Then, according to the material of different metal wires, appropriate electropolishing solutions and parameters are selected for electropolishing. Electropolishing can remove residual micro-scratches and surface stress layers after grinding, while thoroughly removing the oxide film on the surface of the metal wire, obtaining a smooth and activated surface state, providing a good bonding interface for subsequent electroplating.
[0010] The third step is to thicken the plating at both ends of the metal wire sample by electroplating. The areas to be clamped at both ends of the metal wire sample are marked as the plating areas. The length of the plating area along the sample axis is 3~10 cm, which is greater than the clamping width of the clamp and less than the distance between the outer boundary of the gauge length of the sample and the starting position of the clamping end, so as to ensure that the clamp is clamped within the plating area and does not encroach on the gauge length.
[0011] An electroplating solution suitable for this metal wire material is prepared. The electroplating solution is a sulfuric acid-copper sulfate sodium chloride solution. The preparation method is as follows: anhydrous copper sulfate is added to the sulfuric acid solution in portions and stirred to obtain a sulfuric acid-copper sulfate solution. Then, sodium chloride solution is added to obtain the electroplating solution.
[0012] Using a soluble anode plate as the anode and both ends of the metal wire sample as cathodes, the anode and cathode are connected to the positive and negative terminals of a power supply and then immersed in the electroplating solution. The time interval is determined according to the electroplating rate, and then the same operation is performed on the other end. Raising the metal wire sample in sections during the electroplating process avoids stress concentration at the contact point between the liquid surface and the sample due to prolonged electroplating, thus ensuring the accuracy of the tensile test. After electroplating, the diameter of both ends of the metal wire increases by 0.1~1.0 mm.
[0013] The fourth step is post-plating cleaning and drying. After electroplating, rinse the plating surface with alcohol and then blow it dry. Avoid touching the plating with your hands to prevent oxidation.
[0014] Step 5, Tensile Test. The prepared specimen is mounted on a universal testing machine for tensile testing. The clamping position is located at the coating area. The tensile speed is controlled between 1 and 10 mm / min. First, one end of the specimen is placed in the upper clamp. Using the initial contact between the clamp and the specimen as a reference, the clamp is tightened until the specimen neither slips nor deforms. The number of turns of tightening is recorded. The lower clamp is used to clamp the other end of the specimen in the same way. Starting from the initial contact between the clamp and the specimen, the lower clamp is tightened to the same number of turns, ensuring consistent clamping force between the upper and lower clamps until the specimen breaks. The fracture location is recorded, and the tensile strength and elongation are calculated.
[0015] Preferably, in the second step, the electropolishing process involves selecting a suitable electropolishing solution and parameters based on the different metal wire materials to remove the surface oxide film and obtain a smooth, activated surface. The electropolishing solution is a 10% oxalic acid solution with a voltage controlled at 10-20 V; or a perchloric acid-methanol mixture (volume ratio 1:9) with a voltage controlled at 10-20 V; or a perchloric acid-ethanol mixture (volume ratio 1:9) with a voltage controlled at 10-20 V.
[0016] Preferably, in the third step, the electroplating thickening treatment uses a current density of 10~20 A / dm. 2During the electroplating process, the lifting time interval is determined according to the electroplating rate, and the metal wire sample is lifted from the plating solution by 0.5 mm at regular intervals.
[0017] Preferably, in the fifth step of the tensile test, one end of the sample is first placed in the upper clamp. Taking the initial contact between the clamp and the sample as a reference, the clamp is tightened until the sample neither slips nor deforms. The number of turns of tightening the clamp is recorded. The lower clamp clamps the other end of the sample in the same way. Starting from the initial contact between the clamp and the sample, it is tightened to the same number of turns to ensure that the clamping force of the upper and lower clamps is consistent.
[0018] The beneficial effects of this invention are as follows: By electroplating the clamping portions at both ends of the tensile test specimen with thicker material, this invention significantly increases the force-bearing area at the clamping ends, effectively reducing stress concentration at the clamping ends and shifting the tensile fracture location from the clamping ends to within the gauge length. Compared with traditional methods, this invention has the following advantages: First, the pretreatment with electropolishing thoroughly removes the oxide film on the surface of the metal wire, ensuring good adhesion between the coating and the metal substrate and avoiding problems such as coating peeling and flaking. Second, the segmented lifting method used during electroplating avoids stress concentration at the liquid surface due to uneven electric field distribution, ensuring uniform coating quality and accuracy of the tensile test. Third, this method is simple to operate, low in cost, and reliable in effect. It is applicable to the preparation of tensile test specimens of various metal wires with diameters of 0.1~10 mm without requiring modification of the testing machine fixtures or complex specimen clamping operations, and has wide applicability and promotional value. Attached Figure Description
[0019] Figure 1 The image shows a photograph of a copper-plated aluminum alloy wire sample prepared using the method of this invention after a tensile test.
[0020] Figure 2 This is a comparison of the tensile stress-strain curves of copper-plated aluminum alloy wire prepared by the method of this invention and untreated aluminum alloy wire. Detailed Implementation
[0021] The following embodiments will further illustrate the present invention, but are not intended to limit the invention.
[0022] Example 1: Preparation of a tensile specimen of an aluminum alloy wire sample
[0023] (1) Sample cutting and degreasing. Cut a 200 mm long sample from an aluminum alloy wire with a diameter of 3 mm (gauge length 100 mm, clamping length at both ends 50 mm). Wipe the aluminum alloy wire sample repeatedly with alcohol to remove the oil on its surface.
[0024] (2) Electropolishing pretreatment. Mark the 5 cm positions at both ends of the aluminum alloy wire sample as the coating area. First, polish the coating area with 2000# sandpaper. Then, perform electropolishing treatment at room temperature. The electropolishing solution is a mixed solution of perchloric acid and ethanol (volume ratio 1:9). Set the DC voltage to 15 V and the electrolysis time to 1 min to make the surface of the coating area smooth and remove the oxide layer, so as to obtain a smooth and activated surface state.
[0025] (3) Preparation of electroplating solution. Add 300 mL of water to a beaker, slowly add 19 mL of concentrated sulfuric acid, stir and heat, add anhydrous copper sulfate powder in portions while hot, and stir until completely dissolved, for a total of 125 g of copper sulfate; weigh 1 g of sodium chloride, dilute to 100 mL with water, add 6.6 mL of sodium chloride solution to the electroplating solution to introduce chloride ions; after cooling the electroplating solution to room temperature, add water to dilute the solution to 500 mL.
[0026] (4) Copper plating thickening. Using a phosphor bronze anode plate as the anode and one end of the aluminum alloy wire sample as the cathode, the anode and cathode were connected to the positive and negative terminals of the power supply and placed in the electroplating solution. The voltage was controlled at 15 V, and electroplating was carried out for 4 hours. The thickness rate of the plating layer on the surface of the metal wire was controlled by adjusting the current density to ensure that the plating layer was uniform and dense. During this period, the aluminum alloy wire sample was lifted out of the plating solution by 0.5 mm every 1 hour to avoid stress concentration at the contact point between the liquid surface and the sample due to prolonged electroplating. After the electroplating of this end was completed, the same operation was performed on the other end, and electroplating was carried out for another 4 hours. After electroplating, the diameter of the plating part at both ends of the aluminum alloy wire increased from 3 mm to 3.1~3.2 mm (thickening by 0.1~0.2 mm).
[0027] (5) Cleaning and drying after plating. After electroplating, rinse the plating surface with alcohol and dry it with cold air. Avoid touching the plating with your hands. This is called plating layer 1.
[0028] Example 2: Tensile Testing Method for Aluminum Alloy Wire Samples
[0029] The specimen prepared in Example 1 was mounted on a universal testing machine for tensile testing. The clamping position was located at the coated area, and the tensile speed was controlled at 5 mm / min. First, one end of the specimen was placed in the upper clamp. Taking the initial contact between the clamp and the specimen as a reference, the clamp was tightened until the specimen neither slipped nor deformed. The number of turns of tightening the clamp was recorded. The other end of the specimen was clamped in the lower clamp in the same manner, and the clamp was tightened to the same number of turns from the initial contact between the clamp and the specimen to ensure that the clamping force of the upper and lower clamps remained consistent. The specimen fractured within the gauge length, and accurate tensile strength and elongation data were obtained.
[0030] Comparison after tensile testing. Figure 1 These are photographs of copper-plated aluminum alloy wire samples prepared using conventional methods and the method of this invention, after tensile testing. Figure 1 From top to bottom, the images show untreated copper-plated aluminum alloy wire samples before and after a tensile test. The gold-red areas at both ends represent the copper plating layer, while the silver-white area in the middle represents the original aluminum alloy substrate. A comparison reveals that the untreated sample, without the thickening treatment, exhibits obvious clamping indentations at the fracture surface, indicating that the fracture occurred at the clamping end. In contrast, the sample treated with the thickening method of this invention shows no clamping indentations at the fracture surface, indicating that the fracture occurred within the gauge length. The plating layer effectively protects the clamping area from clamping damage.
[0031] Figure 2 This is a comparison of the tensile stress-strain curves of copper-plated aluminum alloy wire prepared using the method of this invention and untreated aluminum alloy wire. Coatings 2 and 3 are parallel samples of copper-plated aluminum alloy wire prepared using the method of Example 1 (the thickening amount is in the range of 0.1~1.0 mm). Original samples 1 and 2 are original aluminum alloy wire samples without electroplating thickening treatment, and tensile tests were performed directly according to the tensile testing method described in this application. Figure 2 It can be seen that the copper-plated samples prepared by the method of the present invention all fractured within the gauge length, and obtained complete stress-strain curves and accurate elongation data; while the original samples without electroplating thickening treatment fractured prematurely near the clamping end due to stress concentration at the clamping end.
Claims
1. A method for preparing a tensile specimen of a metal wire sample, characterized in that, Includes the following steps: The first step is to cut the metal wire sample and remove oil stains from its surface. The second step is to grind and electropolish the two ends of the metal wire sample to be clamped. The third step is to electroplate the two ends of the metal wire sample to be clamped to thicken it. The fourth step is to clean and dry the sample after plating to obtain the tensile test specimen of the metal wire sample.
2. The method for preparing a tensile specimen of a metal wire sample according to claim 1, characterized in that, In the second step, the grinding is done by sanding the clamped area with sandpaper, and the electropolishing is performed at room temperature. The electropolishing solution is a mixed solution of perchloric acid and ethanol with a volume ratio of 1:9, and the DC voltage is set to 15V for 1 minute; or the electropolishing solution is a 10% oxalic acid solution with a voltage of 10-20V for 20-3 seconds; or the electropolishing solution is a methanol solution of perchloric acid with a volume ratio of 1:9, a voltage of 10-20V for 40-50 seconds; or the electropolishing solution is an ethanol solution of perchloric acid with a volume ratio of 1:4, a voltage of 10-20V for 20-30 seconds.
3. The method for preparing a tensile specimen of a metal wire sample according to claim 1, characterized in that, In the third step, the two ends of the metal wire sample to be clamped are marked as the coating area. The length of the coating area along the sample axis is 3~10 cm, which is greater than the clamping width of the clamp and less than the distance between the outer boundary of the gauge length of the sample and the starting position of the clamping end, so as to ensure that the clamp is clamped within the coating area and does not encroach on the gauge length.
4. The method for preparing a tensile specimen of a metal wire sample according to claim 1, characterized in that, In the third step, the two ends of the metal wire sample to be clamped are electroplated to thicken them, and the diameter of the two ends is increased by 0.1~1.0mm.
5. The method for preparing a tensile specimen of a metal wire sample according to claim 1, characterized in that, In the third step, the side surface area of the plated area is calculated based on the diameter of the metal wire and the immersion depth of the plated area. The current density is then determined based on this area, and the current density is controlled between 10 and 20 A / dm². 2 Within the range.
6. The method for preparing a tensile specimen of a metal wire sample according to claim 1, characterized in that, In the third step, the electroplating solution for the thickening treatment is a sulfuric acid-copper sulfate sodium chloride solution. The preparation method is as follows: anhydrous copper sulfate is added to the sulfuric acid solution in portions and stirred to obtain a sulfuric acid-copper sulfate solution. Then, sodium chloride solution is added to obtain the electroplating solution.
7. The method for preparing a tensile specimen of a metal wire sample according to claim 1, characterized in that, In the third step of the electroplating thickening process, the time interval is determined according to the electroplating rate, and the metal wire sample is lifted from the plating solution by 0.5 mm every 1-2 hours.
8. A method for tensile testing of metal wire samples, characterized in that, Place one end of the metal wire sample tensile test specimen as described in any one of claims 1-7 in the upper clamp. With the initial contact between the clamp and the specimen as the reference, tighten the clamp until the specimen neither slips nor deforms. Record the number of turns of tightening the clamp. Clamp the other end of the specimen with the lower clamp in the same manner. Tighten the clamp to the same number of turns from the initial contact between the clamp and the specimen to ensure that the clamping force of the upper and lower clamps is consistent. Perform the tensile test.